Keputusan Muktamar NU (Nahdlatul Ulama') Ke-XXXI dan Fatwa Darul Ifta Mesir Mengenai Penetapan Nasab Anak Melalui Tes DNA (Deoxyribo Nucleic Acid) - Lukito, Bagas (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
The determination of lineage (nasab) in Islamic law is a crucial issue, especially in cases where the paternity of a child is in question. The advancement of science, particularly through DNA testing, has provided a new method for determining lineage. However, this method raises questions regarding its compatibility with Islamic law. This research examines the decisions of the 31st Nahdlatul Ulama (NU) Congress and the fatwa from Darul Ifta Egypt regarding the use of DNA testing for determining lineage. The study aims to analyze the legal basis and implications of these decisions and fatwas in the context of Islamic jurisprudence. The research is normative juridical in nature, using a library research approach. Data sources include primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis technique uses qualitative descriptive analysis with deductive conclusions. The findings indicate that both NU and Darul Ifta Egypt recognize the importance of DNA testing in determining lineage, but with certain conditions and limitations to ensure compliance with Islamic law. The study concludes that DNA testing can be used as a supplementary tool in determining lineage, provided it does not contradict the principles of Islamic jurisprudence.Keywords: DNA Testing, Lineage, Nahdlatul Ulama, Darul Ifta Egypt.